Let p(x) = x^{3} − 2x^{2} − x + 2

All the factors of 2 have to be considered. These are ± 1, ± 2.

By trial method,

p(2) = (2)^{3} − 2(2)^{2} − 2 + 2

= 8 − 8 − 2 + 2 = 0

Therefore, (x − 2) is factor of polynomial p(x).

Let us find the quotient on dividing x^{3} − 2x^{2} − x + 2 by x − 2.

By long division,

It is known that,

Dividend = Divisor × Quotient + Remainder

∴ x^{3} − 2x^{2} − x + 2 = (x + 1) (x^{2} − 3x + 2) + 0 = (x + 1) [x^{2} − 2x − x + 2]

= (x + 1) [x (x − 2) − 1 (x − 2)] = (x + 1) (x − 1) (x − 2)

= (x − 2) (x − 1) (x + 1)